Designing a new dimerized anti human TNF‐α aptamer with blocking activity. (10th March 2020) - Mashayekhi, Kazem; Ganji, Ali; Sankian, Mojtaba
Abstract: The human tumor necrosis factor α (hTNF‐α) is an important pro‐inflammatory cytokine which plays critical roles in inflammatory diseases such as rheumatoid arthritis (RA). The anti‐TNF‐α proteins can reduce symptoms of RA. Due to limitations of protein‐based therapies, it is necessary to find new anti‐TNF‐α agents instead of common anti‐TNF‐α proteins. Therefore, the aim of the current study was to identify a new DNA aptamer with anti‐hTNF‐α activity. The protein systematic evolution of ligands by exponential enrichment (SELEX) process was used for identifying DNA aptamers. Anti‐hTNF‐α aptamers were selected using dot blot, real‐time PCR, and in vitro inhibitory assay. The selected aptamers were truncated in two steps, and finally, a dimer aptamer was constructed from different selected truncates to improve their inhibitory effect. Also, Etanercept was used as a positive control to inhibit TNF‐α, in comparison to the designed aptamers. After 11 rounds, four aptamers with anti‐hTNF‐α inhibitory effect were identified. The truncation and dimerization strategy revealed a new dimer aptamer with 67 nM K d, which has 40% inhibitory effect compared with Etanercept (60%). Overall, the dimerization and truncation aptamers could improve its activity. With regard to the several limitations of anti‐TNF‐α proteins therapies including immunogenicity, side effects, and cost‐intensive, a new designed anti‐hTNF‐α dimer aptamer could be considered as a potential therapeutic and/or diagnostic agent for hTNF‐α‐related disorders.